Answer:
y = -3
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Explanation:
Step 1: Define
-8 = 2y - 2
Step 2: Solve for y
- [Addition Property of Equality] Add 2 on both sides: -6 = 2y
- [Division Property of Equality] Divide 2 on both sides: -3 = y
- Rewrite/Rearrange: y = -3
Step 3: Check
Plug in y into the original equation to verify it's a solution.
- Substitute in y: -8 = 2(-3) - 2
- Multiply: -8 = -6 - 2
- Subtract: -8 = -8
Here we see that -8 does indeed equal -8.
∴ y = -3 is the solution to the equation.